Microsomal pre‐receptor cortisol production is inhibited by resveratrol and epigallocatechin gallate through different mechanisms. (29th November 2018) - Szelényi, Péter; Somogyi, Anna; Sarnyai, Farkas; Zámbó, Veronika; Simon‐Szabó, Laura; Kereszturi, Éva; Csala, Miklós
Abstract: Local activation of cortisol in hormone target tissues is a major determinant of glucocorticoid effect. Disorders in this peripheral cortisol metabolism play an important role in the development of metabolic diseases, such as obesity or type 2 diabetes mellitus. Hence, dietary factors influencing the activity of the involved enzymes can have major impacts on the risk of the above diseases. Resveratrol and epigallocatechin gallate (EGCG), two natural polyphenols found in several nutriments and in green tea, respectively, are well‐known for their antiobesity and antidiabetic activities. EGCG has been shown to interfere with microsomal cortisol production through decreasing the luminal NADPH:NADP + ratio. The aim of this study was to clarify if resveratrol also induces such a redox shift or causes any direct enzyme inhibition that influences local cortisol production. Cortisone–cortisol conversions and changes in NADPH levels were monitored in rat liver microsomal vesicles. Cortisol production was inhibited by resveratrol in a concentration dependent manner while the intrinsic reducing and oxidizing capacity as well as the NADPH level inside the ER‐derived vesicles remained unaffected. Activity measurements performed in permeabilized microsomes confirmed that resveratrol, unlike EGCG, inhibits 11β‐hydroxysteroid dehydrogenase type 1 directly. Long‐term moderation of pre‐receptor cortisol production likely contributes to the beneficial health effects of both polyphenols. © 2018 BioFactors, 45(2):236–243, 2019